HUBUNGAN ANTARA REGULASI DIRI DENGAN PERILAKU PROKRASTINASI AKADEMIK PADA MAHASISWA SEKOLAH TINGGI ILMU KESEHATAN (STIKES) MITRA ADIGUNA PALEMBANG - Fitriya Fitriya; Lukmawati Lukmawati (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2016)
Individuals who have difficulty to do anything within the limits of the allotted time , often delayed , prepare something with very excessive and failed to complete the task within the limits of a predetermined time , say as an individual who does procrastination. Therefore , procrastination can be regarded as one of the behaviors that are not efficient in the use of time and their tendency not to immediately start a job when facing a task.This study aims to test empirically whether there is a correlation between self-regulation with academic procrastination. Self-regulation is the independent variable, while the dependent variable is the academic procrastination. The population in this study is 190 students study program diploma of Nursing STIKES MItra Adiguna Mitra Palembang, and the sample was 123 students study program diploma of Nursing STIKES Adiguna Palembang.The results of the analysis obtained correlation coefficient of r = -0.755 and significance of p = 0.000 , it’s mean p <0.01 , so the hypothesis is proven or accepted, it can be concluded that there is a significant negative correlation between self-regulation with academic procrastination behavior in students Science Colleges Health of Mitra Adiguna Palembang.